Roosevelt : the party leader, 1932-1945 - Savage, Sean J., 1964- (Lexington : The University Press of Kentucky, 2015)
FDR -- the wily political opportunist glowing with charismatic charm, a leader venerated and hated with equal vigor -- such is one common notion of a president elected to an unprecedented four terms. But in this first comprehensive study of Roosevelt's leadership of the Democratic party, Sean Savage reveals a different man. He contends that, far from being a mere opportunist, Roosevelt brought to the party a conscious agenda, a longterm strategy of creating a liberal Democracy that would be an enduring majority force in American politics. The roots of Roosevelt's plan for the party ran back to.
Tom Pendergast and the Demise of a MachineEd Flynn and New York Politics; The Bosses and a Liberal Democratic Party; 4 Roosevelt and the Democratic National Committee; FDR's Concept of the DNC's Role; The DNC under Parley; DNC Finances (1932-1944); Special DNC Divisions; DNC Chairmen (1932-1945); 5 The Formation of an Electoral Coalition, 1932-1936; The 1932 Election; The 1936 Election; 6 The Purge Campaigns of 1938; 7 The Struggle to Maintain a Liberal Party, 1940-1944; The 1940 Election; The 1944 Election; Epilogue: FDR's Legacy in the Democratic Party; Notes; Index.
Print version record.
JSTOR
Keywords: Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945; Political leadership -- United States -- History -- 20th century; United States -- Politics and government -- 1933-1945.; États-Unis -- Politique et gouvernement -- 1933-1945.; HISTORY -- United States -- State & Local -- General; POLITICAL SCIENCE -- Political Process -- Political Parties; Political leadership; Politics and government; United States; 1900-1999; History